2020
DOI: 10.5897/ajar2020.14959
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and restrictions of range pasture improvement by agro-pastoralists in Kiruhura District, Uganda

Abstract: Range pastures provide the basic ruminant feeds resource for livestock production in semi-arid areas despite ruminant nutrition remaining a challenge affecting productivity. Different livestock development interventions have been promoted to improve livestock nutrition with low farmer adoption rate. A cross sectional exploratory study was conducted between March and July 2018 to identify the drivers of range pastures improvement technologies adoption in rangelands with specific objectives as: (a) Assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Land use influences the nutrient distribution and their supply by causing the alteration of the soil property and controlling the activity of microbes near the root zones. Cultivation causes the soil carbon to diminish within a few years of the conversion (Murty et al, 2002), reducing carbon sequestration (Robert et al, 2020) and can substantially lower the mineralizable soil nitrogen (Richter et al, 2000). The topsoil organic diminishes, thus reducing the productivity (Majaliwa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Land use influences the nutrient distribution and their supply by causing the alteration of the soil property and controlling the activity of microbes near the root zones. Cultivation causes the soil carbon to diminish within a few years of the conversion (Murty et al, 2002), reducing carbon sequestration (Robert et al, 2020) and can substantially lower the mineralizable soil nitrogen (Richter et al, 2000). The topsoil organic diminishes, thus reducing the productivity (Majaliwa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For South-western Uganda, it is reported that in the last decade, there were efforts of improving the productivity of range pastures through the dryland husbandry project. The project promoted practices which included pasture establishment; organic manuring, water harvesting, over-sowing and reseeding; legume pasture seed production and erosion control (Twinamasiko et al, 2020). Without clear explanation, there was unanticipated drop out of implementation of pasture improvement practices and technologies by livestock farmers upon the project expiry.…”
Section: Introductionmentioning
confidence: 99%